Creación de un programa de deportes para televisión para promover una vida saludable. - Sagnaí Orbe, Henry Roberto (2016)
The present work goes directed towards the creation of a television program, in which there appears step by step the process of construction that is carried out at the moment of capturing on the screen a project directed to entertain and to inform the receiving public. Pre production, production and post production they are detailed in the following report, which explains in a clear way the work that is realized in television, technical, logistic and human aspects that were indispensable for the creation of the sports program. The genre that was taken into consideration for this proposal is an entertainment - informative, thought in a weekly regularity and it takes as a target to encourage to the citizenship to the sports practice, this way to obtain a better life style. A dynamic and lively format is the one that is projected in the PURO DEPORTE program, its presenters are the managers of leading the viewer to living and knowing to figures of the national sport, new and entertaining sports, advices and tips to be healthy and especially they take the message of which all the persons, from children up to major adults can be a part of a healthy life style. A fresh and different proposal that hopes to leave in the viewer the motivation and desire of realizing any sport and this way to stay healthy and happy.